Effectiveness of Learning Nihonggo as A Foreign Language Among Third-Year BS Tourism Management Students at Bestlink College of the Philippines: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study discusses Determine the Effectiveness of Learning Nihongo as a Foreign Language Subject in Bestlink College of the Philippines Bachelor of Science in Tourism Management. It analyses how tourism students can converse with foreign visitors using the language of Nihongo, culture, and beliefs. Thus, the study aims to understand tourism students' perceptions of learning Nihongo. Foreign language abilities make pupils more valuable in the marketplace by allowing them to interact with people from various cultures to develop a more thorough understanding of their culture someday. The survey results help researchers develop an essential suggested measure to improve their foreign language abilities.